A spider hanging inside a carbon cage: off-center shift and pyramidalization of Sc3N clusters inside C84 and C86 fullerene cages. Issue 19 (17th August 2022) - Fu, Ze; Guo, Min; Yao, Yang-Rong; Meng, Qingyu; Yan, Yingjing; Wang, Qin; Shen, Yi; Chen, Ning
Abstract : Structural analysis shows that, in Sc3 N@ C s (51365)-C84 and Sc3 N@ D 3 (19)-C86, the Sc3 N clusters are shifted to one side of the cages and unexpectedly pyramidalized inside the large cages of C84 and C86, which resembles a spider attached to a web. Abstract : Metal nitride cluster fullerenes (NCFs) are the most intensively studied endohedral fullerenes due to their exceptional structural variety. It is commonly understood that in NCFs, small clusters such as Sc3 N favor C82 and smaller cages, while large clusters ( e.g., Tb3 N and Gd3 N) favor C84 and larger cages. Endohedral structures with small nitride clusters encaged inside large carbon cages ( e.g., C84 and C86 ), although theoretically probed, have never been experimentally obtained. Herein, we report two novel NCFs, Sc3 N@ C s (51365)-C84 and Sc3 N@ D 3 (19)-C86, which have been successfully synthesized and characterized using MALDI-TOF mass spectrometry, X-ray single-crystal diffraction and UV–vis–NIR spectroscopy. Crystallographic analysis shows that, while in most previously reported cluster fullerenes, clusters tend to take a central position inside fullerene cages, in these two structures, the Sc3 N clusters are shifted to one side of the cage and unexpectedly pyramidalized inside the large cages of C84 and C86, which resembles a spider hanging inside a carbon cage. These observations, together with the stretched Sc–N bonds, suggest that the M3 N cluster can self-adjust not only its configuration but also its position relative to fullerenes to optimize the metal–cage distances as well as cluster–cage interactions, thus promoting the stability of endohedral structures. This work provides new insight into the interaction mechanisms between the clusters and carbon cages of endohedral fullerenes.